LACTOBACILLUS SPECIES MTCC 10093 AS A MODEL BACTERIUM FOR THE BIOREMEDIATION OF ARSENIC IN AGRICULTURAL FIELD. - BINOD KUMAR,; UJJAL KUMAR GHOSH, (The Bioscan, 2020)
The Soil inhabiting Lactobacillus readily isolated and characterized on the basis of biochemical and molecular study. It has found that this strain is also exhibits tolerance against Arsenic. It can grow at high concentrations of arsenite (AsIII) ranging from 2 ppm to 20 ppm (part per million). The positive silver nitrate (AgNo 3 ) test has revealed oxidizing capacity of strain. No extra band of protein in either stressed or non-stressed condition noticed in protein profile. We noticed maximum tolerance concentration (MTC)s of this bacterium is 20 ppm. This strain is also resistance against antibiotic Streptomycin and Nalidixic acid. The strain has been identified as Lactobacillus rhamnosus MTCC 10093 (NCBI Gene Bank Accession No: KT982211). Its arsenic oxidizing capacity could be exploited for bioremediation of arsenic in agricultural field.